Consumers attitude towards life insurance / Mohamad Kamil Ariff Khalid - Khalid, Mohamad Kamil Ariff (2001)
Consumers today have a greater access to abroad range of savings and investment options. Insurance players will soon find that the more successful they are in meeting their customers’ diverse financial needs, the more effective they will be in meeting theirs customers’ insurance needs. Insurance players are also poised to become primary of developments in innovative financial solutions. By acquiring an intimate knowledge of consumers’ attitudes, needs and wants, consumers’ preferences and demand, insurance players can make an invaluable contribution to the development of new product. In order to change the negative attitude of Malays towards life insurance, efforts should be made to strengthen of all the weaken factors in the life insurance industry.